Effectiveness of Household Landslide Preparedness Education on the Preparedness Capacity of Families - Permana, Iwan; Mohd Said, Faridah; Umar, Syazana (KnE Social Sciences, 2023)
Disasters are events that threaten and disrupt people’s lives and livelihoods due to natural and/or non-natural factors as well as human factors that cause human casualties, environmental damage, property losses, and psychological. The implementation of disaster preparedness has not been carried out comprehensively and continuously throughout Indonesia. This study aimed to determine the effectiveness of landslide preparedness education interventions in increasing the landslide preparedness capacity of households in the Sukabumi Regency. The minimum sample was 118 for each intervention and control group. Random sampling was used for sampling technique. Data analysis was done using an independent t-test. The results of the study mean that the difference in knowledge scores showed a significant difference between the intervention group and the control group (F = 23.41, p-value = 0.000). In addition, the average difference in household preparedness scores for landslides showed a significant difference between the intervention and control groups (F = 190.08, p-value = 0.000). After the intervention, the intervention group’s household disaster preparedness improved significantly. Meanwhile, no significant increase was observed in the control group’s household disaster preparedness score after the intervention. Household disaster preparedness training may have an impact on the knowledge, attitudes, and behavior of individuals and families. Trainings such as online and simulation using live or recorded demonstrations should be developed and evaluated for their effectiveness. Keywords: household landslide preparedness, education, preparedness capacity